Aortic Valve Replacement in Elderly Patients With Small Aortic Annulus: Results With Three Different Bioprostheses. Issue 1 (February 2019) - Chiariello, Giovanni A.; Bruno, Piergiorgio; Villa, Emmanuel; Pasquini, Annalisa; Pavone, Natalia; Cammertoni, Federico; Mazza, Andrea; Colizzi, Christian; Nesta, Marialisa; Iafrancesco, Mauro; Perri, Gianluigi; Messina, Antonio; et al.
Abstract : Objectives: Aortic valve replacement (AVR) in patients with small aortic annulus (diameter ≤21 mm) is considered a challenging scenario because of technical aspects and the high risk of patient-prosthesis mismatch (PPM). The choice of the appropriate prosthesis is crucial, and at the moment, an ideal device has yet to be identified. We compare clinical and hemodynamic results after AVR with three bioprostheses with different design and characteristics. Methods: We retrospectively evaluated 76 consecutive patients from two cardiac surgery centers who underwent AVR (Trifecta = 24; Edwards INTUITY Elite valve system = 26, and Perceval = 26) for severe aortic stenosis between 2013 and 2017. Patients selected were older than 75 years and with an annulus diameter ≤21 mm at preoperative echocardiogram. Reinterventions and combined procedures were excluded. Minimally invasive AVR was performed in 44 (57.8%) patients. Telephonic interview was obtained at 2.9 ± 0.5 years and echocardiographic follow-up at 2.2 ± 0.8 years. Results: Clinical outcome was similar in the three groups. At follow-up, Trifecta patients presented significantly higher peak and mean transprosthetic pressure gradients ( P = 0.04 and 0.01). Effective orifice area and left ventricular mass regression were comparable, although an advantage was observed in Perceval patients without reaching the statistical significance. Incidence of moderate ( P = 0.2) and severe PPM ( P = 0.7) was comparable. Conclusions: Despite higher postoperative pressure gradients observed with the Trifecta valve, all three prostheses (Trifecta, Edwards INTUITY Elite, and Perceval) have proven to be reliable when implanted in small aortic annuli, with good clinical outcome and favorable left ventricular mass regression.